Novel aggregated controller of wind and PV based grid connected charging station for electric vehicle - Deepak, Karanam; Mandal, Rajib Kumar; Verma, Vimlesh (International Journal of Power Electronics and Drive Systems (IJPEDS), 2023)
Novel technologies are adopting electric vehicles (EVs) day-by-day due to increasing interest in EVs. The charging process of EVs is a very important aspect when it is connected to the utility grid. Generally charging of an EV can be done at either home or in charging stations were connected to the utility grid. More harmonics and nonlinear currents are injecting into the utility grid during the charging process of the battery due to the existence of converters for power conversion in charging stations of EVs, which generally affects the quality of the power. In this situation, supplying the power to the utility grid from batteries existing in the vehicle through the charging station will provide a better solution and will charge again when there is less demand on the grid. Further using renewable energies in the charging stations can provide reliable power for both vehicles as well as the utility grid. To achieve better performance and maintain power quality at load bus, an aggregated controller is proposed in this paper. Moreover, reloading conditions are also incorporated to renewable energy sources under disconnection of the utility grid to maintain power balance. Hardware-in the–loop (HIL) based extensive results by using OPAL-RT modules are examined in this article under many situations to validate the proposed method.